APOBEC3 selects V179I in HIV-1 reverse transcriptase to provide selective advantage for non-nucleoside reverse transcriptase inhibitor-resistant mutants - Dwivedi, Richa; Wang, Youya; Kline, Christopher; Fischer, Douglas K.; Ambrose, Zandrea (Frontiers in Virology, 2022)
The V179I substitution in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) is selected in humans or mouse models treated with certain nonnucleoside reverse transcriptase inhibitors (NNRTIs). While it is often observed together with other NNRTI resistance mutations, V179I does not confer drug resistance. To understand how V179I arises during NNRTI treatment, we characterized it in HIV-1 molecular clones with or without the NNRTI resistance mutations Y181C or Y181V. While V179I alone did not confer resistance to any NNRTIs tested, when present with Y181C/V it enhanced drug resistance to some NNRTIs by 3- to 8-fold. In replication competition experiments in the presence of the NNRTI rilpivirine (RPV), V179I modestly enhanced Y181C HIV-1 or Y181V HIV-1 replication compared to viruses without V179I. As V179I arises from a G to A mutation, we evaluated whether it could arise due to host APOBEC3 deaminase activity and be maintained in the presence of a NNRTI to provide a selective advantage for the virus. V179I was detected in some humanized mice treated with RPV and was associated with G to A mutations characteristic of APOBEC3 activity. In RPV selection experiments, the frequency of V179I in HIV-1 was accelerated in CD4+ T cells expressing higher APOBEC3F and APOBEC3G levels. Our results provide evidence that V179I in HIV-1 RT can arise due to APOBEC-mediated G to A hypermutation and can confer a selective advantage to drug-resistant HIV-1 isolates in the presence of some NNRTIs.